2016
DOI: 10.1371/journal.pone.0155118
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcodes Confirm the Taxonomic and Conservation Status of a Species of Tree on the Brink of Extinction in the Pacific

Abstract: The taxonomic status of a single island, narrow range endemic plant species from Palau, Micronesia (Timonius salsedoi) was assessed using DNA barcode markers, additional plastid loci, and morphology in order to verify its conservation status. DNA barcode loci distinguished T. salsedoi from all other Timonius species sampled from Palau, and were supported by sequence data from the atpB-rbcL intergenic spacer region. Timonius salsedoi was only known from two mature individual trees in 2012. Due to its extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Even though the earth may be undergoing its sixth major extinction with extinction rates over 1000 times normal (Wilson, ), observing a species extinction event is rare. Plant DNA barcodes were used to verify that a narrow range endemic tree in the family Rubiaceae, known only from two mature individuals on the island of Palau in Micronesia, was most likely a distinct species in the genus Timonius (Costion et al, ). Additional morphological and molecular data verified that this taxon was T. salsedoi Fosberg & Sachet described in the 1980s.…”
Section: Hotspots In the Application Of Plant Dna Barcodes Todaymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the earth may be undergoing its sixth major extinction with extinction rates over 1000 times normal (Wilson, ), observing a species extinction event is rare. Plant DNA barcodes were used to verify that a narrow range endemic tree in the family Rubiaceae, known only from two mature individuals on the island of Palau in Micronesia, was most likely a distinct species in the genus Timonius (Costion et al, ). Additional morphological and molecular data verified that this taxon was T. salsedoi Fosberg & Sachet described in the 1980s.…”
Section: Hotspots In the Application Of Plant Dna Barcodes Todaymentioning
confidence: 99%
“…In 2014 after a survey of the island where these two individuals were known to occur it was discovered that both trees had succumbed when a typhoon hit the area. Previously recommended as Critically Endangered by IUCN criteria, it is now suspected that this species is extinct (Costion et al, ).…”
Section: Hotspots In the Application Of Plant Dna Barcodes Todaymentioning
confidence: 99%
“…For plants the extinction of only 571 species over the last several hundred years has been carefully documented [180]. On the island of Palau in Micronesia, plant DNA barcodes were used to verify that a narrow range endemic tree described in the 1980s known from only two mature individuals was Timonius salsedoi Fosberg and Sachet in the family Rubiaceae [181]. Subsequently, after a typhoon hit the area, a survey of the island revealed that both trees had perished.…”
Section: Conservation Assessmentmentioning
confidence: 99%
“…Thereafter, trnH-psbA and ITS (or ITS2) were suggested as complementary markers to the core barcode of rbcL + matK [259]. Later, some studies concentrated on evaluating the identification capability of specific groups using these four barcode loci [260][261][262][263][264], and others have focused on the discovery of new markers suitable for a given taxa [265][266][267].…”
Section: Dna Barcoding In Bamboosmentioning
confidence: 99%